Stem cells: basic research on health, from ethics to panacea - Naara Luna; Thaddeus Blanchette (Faculdade de Medicina de Botucatu (Unesp), 2007)
Even though stem cell therapies are still under experimentation, the media has represented them as a panacea that would cure all diseases. This fact secured the authorization for using human embryos as research material. Therapies include manipulation of human material in tissue bioengineering, suggesting a representation of the body as a factory. This article describes stem cell research projects being carried out in the health sciences center of a higher education institution, focusing on field organization and on the system of values underlying scientific activity. Researchers at different levels were interviewed about perspectives on, and implications of, their research in order to analyze the discourse of the projects' participants. Experiments with adult stem cells enjoyed wide support, while the use of human embryos was disputed. The foundations of those arguments were sought in their relation both to the structure of the scientific field and to the researchers' religious background.